2017
DOI: 10.1038/s41598-017-05702-5
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome analysis identifies differentially expressed genes related to lipid metabolism in Wagyu and Holstein cattle

Abstract: Fat deposition of beef cattle varies between breeds. However, the regulation mechanism is still not elucidated completely at molecular level. In the present study, we comparatively analyzed transcriptome of subcutaneous adipose tissue between Wagyu and Holstein cattle with a significant difference in fat deposition to identify key genes associated with fat metabolism and adipogenesis by high-throughput RNA-seq technology. A total of 59,149,852 and 69,947,982 high quality reads were generated, respectively. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 74 publications
4
55
0
Order By: Relevance
“…Moreover, they play a role in the regulation of adipocyte differentiation and lipid metabolism (Huang et al . ,b; Muret et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they play a role in the regulation of adipocyte differentiation and lipid metabolism (Huang et al . ,b; Muret et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The precise understanding of the cascade of these molecular events and the way to regulate them will be crucial for efficiently treating obesity. PPAR signaling pathway is a key pathway closely associated with metabolism of fatty acid and sterols, and adipogenic differentiation [21,55,56]. Lim et al used qRT-PCR to analyze the genes associated with PPAR signaling pathway in the longissimus dorsi muscle of Hanwoo cattle [57].…”
Section: Pigsmentioning
confidence: 99%
“…LncRNAs, nonprotein coding transcripts longer than 200 nucleotides, have important regulatory functions in adipogenesis and lipid metabolism. With the development of high throughput sequencing technology, RNA-seq has been widely applied in the identification and functional analysis of lncRNAs and mRNAs of adipose tissues in pig [7,13,16,17], chicken [18], sheep [19,20] and cattle [21]. Ramayo et al [22] identified 270 and 186 lncRNAs in the liver tissues of female pigs with high and low intramuscular fatty acid contents, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been an increase in the utilization of Next Generation Sequencing (NGS) to examine the transcriptome for the identification of differential expression as well as for the opportunity to discover novel transcripts, including new alternative isoforms and miRNAs [14][15][16][17][18][19][20][21][22][23][24][25][26]. Therefore, in the present study, a comparison of the miRNA profiles of the adipose tissue of the Laiwu pig and Large White pig was performed using RNA-seq.…”
Section: Introductionmentioning
confidence: 99%